Publishing studies: being part of a cultural practice plus x ? (Libellarium: journal for research in the field of information and related sciences, 2015)
In some parts of the world, Publishing Studies are a fairly well-established field of research as well as of higher education. Not least since this is not so much the case in continental Europe, the Publishing Studies community increasingly sees a more elaborated self-concept as an important prerequisite for a prosperous further development of the field in research as well as in teaching. This paper starts off by relating the question for an advanced self-concept of Publishing Studies to the question what criteria have to be fulfilled to call a field (like Publishing Studies) a scholarly discipline. As the second source for the possible formation of a more elaborate self-concept, the paper presents the first results of an ongoing empirical research project. In this projects, extensive expert interviews with representatives of UK Publishing Studies study programs and research institutions are evaluated to shed light on the core questions related to Publishing Studies as a discipline / „discipline“ in a bottom-up manner. After presenting a very clear and differentiated North American view as an additional point of reference, a contribution to the discussion on Publishing Studies is proposed.
Keywords: publishing studies; publishing studies self-conception; scientific discipline